Amazing pace : the story of Olympic champion Michael Phelps, from Sydney to Athens to Beijing - McMullen, Paul, 1955- (Rodale : Distributed to the trade by Holtzbrinck, 2006)
Chronicles American swimmer Michael Phelps's last year of preparation for the 2004 Athens Olympics, his battles for gold there, and the medical and legal problems he faced in the months afterward.